Efektivitas Penerapan Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) pada Pemerintahan Daerah Kota Bandung (Studi Kasus pada Badan Kepegawaian, Pendidikan dan Pelatihan; Bagian Umum dan Perlengkapan dan Badan Kesatuan Bangsa dan Politik) - Yunita Christy; Sinta Setiana; Puput Cintia (Jurnal Akuntansi, 2017)
AbstractThe creation of a good governance system (one good way of governance) one of the way with a good performance measurement system to support the implementation. The government then makes a performance measurement system that is Government Accountability System of Performance Institution (SAKIP). The final product of SAKIP that describes the performance achieved by a government agency on the implementation of programs and activities funded by APBN/APBD is known as LAKIP (Performance Accountability Report of Government Agencies). The number of Regional Device Units incorporated in the city or county governments throughout Indonesia, it was reported that no one had achieved an A rating of the LAKIP he had compiled. This phenomenon forms the basis for our research to attempt to disclose other factors that might influence the assessment of LAKIP on the performance appraisal system for SKPD in Indonesia. Based on previous research conducted by Spekle and Verbeeten (2013), this study tried to replicate to test whether it yielded the same conclusions. Sample amounted to 127 comes from population 3 SKPD in Bandung with data analysis technique Moderated Regression Analysis (MRA). The results showed that SAKIP oriented incentives did not affect the performance of civil servants. SAKIP-oriented exploration affects the performance of civil servants. Contractibility as a moderating variable can not strengthen or weaken the relationship of SAKIP oriented incentives tocivil servants performance while the relationship SAKIP oriented exploration and performance of civil servants negativf influence. Input for the next researcher so as not to focus on one office and test the variables in this study on different settings and is expected to increase the number of samples to obtain better resultsKeywords: Government Agency Performance Accountability System (SAKIP), Performance,     Contractibility, SKPD   Bandung